2016
DOI: 10.1159/000453581
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Skin and Plasma Advanced Glycation End Products and Their Associations with Arterial Stiffness

Abstract: Background: We compared skin and plasma measurements of advanced glycation end products (AGEs), with particular focus on their levels in the presence of hypertension or diabetes and prediabetes and their associations with arterial stiffness in outpatients with suspected or diagnosed hypertension. Methods: Skin AGE accumulation was measured as autofluorescence on the left forearm using the skin autofluorescence Reader and expressed in arbitrary units in the range from 0 to 25. Plasma AGE concentration was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The antiglycation effect is known to be associated with vasorelaxation via improvement of atrial stiffness since AGEs are a proven marker of CVD, diabetes, and hypertension [ 50 ]. From a study with Chinese subjects, plasma AGE concentration was found to be positively correlated with pulse wave velocity from the carotid to femoral arteries [ 51 ]. More interestingly, the serum TG level was elevated under conditions of high plasma AGE content.…”
Section: Discussionmentioning
confidence: 99%
“…The antiglycation effect is known to be associated with vasorelaxation via improvement of atrial stiffness since AGEs are a proven marker of CVD, diabetes, and hypertension [ 50 ]. From a study with Chinese subjects, plasma AGE concentration was found to be positively correlated with pulse wave velocity from the carotid to femoral arteries [ 51 ]. More interestingly, the serum TG level was elevated under conditions of high plasma AGE content.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, AGEs' assays are mostly based on the use of specific antibodies or spectrofluorimetric measurements based on the fluorescent properties of AGEs [212, 213]. Although promising results came from studies on skin autofluorescence in diabetic patients [214, 215], the serum fluorescence AGE (F-AGE) method did not distinguish women with gestational diabetes from the healthy controls [216]. …”
Section: Markers Based On Ros-induced Modificationsmentioning
confidence: 99%
“…In addition to the classic Maillard reaction, AGEs are formed through the reaction of amino groups with α-dicarbonyls, such as 3-deoxyglucosone, methylglyoxal and glyoxal [ 8 10 ]. AGEs may form cross-links between tissue proteins in the vascular wall, causing increased vascular stiffness and elevated BP [ 11 , 12 ]. Moreover, binding of circulating AGE to its receptor (receptor for AGE [RAGE]) and uptake into the vessel wall may accelerate the progression of atherosclerosis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%